INFUSED WATER ANGGUR MERAH (Vitis Vinifera) MENINGKATKAN pH PLAK DAN pH SALIVA - Kurnia Budi Kurniawan; Diyah Fatmasari (Poltekkes Kemenkes Semarang, 2018)
Plaque accumulation on tooth surfaces associated with plaque pH and saliva pH. A decrease in the pH plaque and pH saliva will continually cause demineralization. One effort to prevent the plaque accumulation by consuming fruits. Infused water is a preparation made from the extract of fruits in mineral water.Purpose of this study to investigate the effect of consuming red grape (Vitis Vinifera) infused water to the plaque pH and salivary pH. Research design was a quasi-experimental design with pre-post test control group. Research conducted 16 on students Orphanage Aisyiyah as sample and simple random sampling as saple collection. Sampes was instructed to consume red grape infused water and saliva pH and plaque pH were counted before and after consuming red grape infused water. Data were analyzed with paired sample test with significance level of 5%.The results showed mean of plaquepH before and after consuming red grape infused water is 6.04 and 7.06. The study also found mean salivapH before and after consuming red grape infused water is 6.01 and 7.26.Paired samples get significant value of p less than 0.05 (ρ = 0.001 plaque pH and saliva pH ρ = 0.002. The conclusion of this study, there are significant effect of consuming red grape infused water to enhancement of plaque pH and salivary pH